THE INFLUENCE OF PERCEPTION OF BUDGET PLANNING AND BUDGET IMPLEMENTATION ON BUDGET PERFORMANCE THROUGH APPLICATION OF BUDGET EXPENDITURE IN PUBLIC HEALT DEPARTMENT BONDOWOSO DISTRICT. - Anton Asmara, Raden Andi Sularso & Yosefa Sayekti (International Journal of Research Science and Management, 2018)
Currently, there are still many public sector budget performances that show the realization of budget performance optimally. The government must be able to manage the state's wealth professionally and accountably for a dynamic balance in order to carry out government activities to achieve a just and prosperous society both material and spiritually based on the 5th principle of Pancasila and the 1945 Constitution. This study aims to analyze the effect of budget planning perceptions and budget execution on budget performance through the absorption of budget spending at Bondowoso District Health Office. With the number of Regional Technical Implementation Unit (UPTD) which amounts to 25 health centers. It also aims to determine the best strategy in budget planning and budget implementation in order to achieve optimal budget performance. This research includes research with quantitative approach with hypothesis testing that is causality. Quantitative method of this study is using Path Analysis. Sampling in this study using the census method is to take the entire sample of 52 respondents. The data used are primary data collected through questionnaire. The results of this study indicate that the implementation of the budget has no significant effect on the absorption of budget spending. Budget execution has no significant effect on budget performance. While budget planning has a positive effect on the absorption of budget spending, budget planning has a positive effect on budget performance. And expenditure absorption has a positive effect on budget performance. The result of quantitative analysis concluded that Puskesmas is not optimal in managing National Health Insurance capitation fund (JKN). To overcome these obstacles / difficulties is done with a policy strategy that can improve the performance of an optimal budget